Assessment of municipal solid waste for valorization into biofuels. Issue 4 (22nd June 2019) - Thompson, Vicki S.; Ray, Allison E.; Hoover, Amber; Emerson, Rachel; Hartley, Damon; Lacey, Jeffrey A.; Yancey, Neal; Thompson, David N.
Abstract: Almost 36 million tons of paper and yard trimmings are not currently being recycled or composted annually and likely end up in landfills. One approach to valorize these resources would be for biofuels production. Nonrecyclable municipal solid waste (MSW) paper and yard trimmings were assessed for their suitability as feedstocks to produce biofuels from sugars. Both materials met the cost target of less than $85.51/ton ($2016) with MSW paper ranging from $36.40 to $62.18/dry ton and grass clippings from $25.64 to $45.86/dry ton. MSW paper exceeded the carbohydrate requirement of 59% while grass clippings had significantly lower amounts of carbohydrates (30%). However, both types of MSW had ash contents significantly above the required 5% total ash with paper at 22% ash and grass clippings at 16%. While neither waste material was individually found to be suitable for biofuels production based on compositional requirements, it was determined that blending either waste with corn stover would produce materials that met carbohydrate, ash, and cost targets. The higher carbohydrate and lower ash stover compensated for the lower carbohydrates and high ash of the waste materials, while the lower cost waste materials offset the higher cost of corn stover.